2016
DOI: 10.1098/rsbl.2015.0646
|View full text |Cite
|
Sign up to set email alerts
|

Photoautotrophic microorganisms as a carbon source for temperate soil invertebrates

Abstract: We tested experimentally if photoautotrophic microorganisms are a carbon source for invertebrates in temperate soils. We exposed forest or arable soils to a 13 CO 2 -enriched atmosphere and quantified 13C assimilation by three common animal groups: earthworms (Oligochaeta), springtails (Hexapoda) and slugs (Gastropoda). Endogeic earthworms (Allolobophora chlorotica) and hemiedaphic springtails (Ceratophysella denticulata) were highly 13 C enriched when incubated under light, deriving up to 3.0 and 17.0%, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…), may feed on non‐vascular plants, i.e. algae and lichens, suggesting that the importance of non‐vascular plants as a basal resource of soil food webs has been underestimated (Schmidt et al ., ; Potapov et al ., ; Potapov et al ., ). Supporting the importance of non‐vascular plants in soil food webs, a recent DNA‐based study showed that algivory is widespread among soil protists (Seppey et al ., ).…”
Section: Reconstructing Trophic Linksmentioning
confidence: 98%
See 1 more Smart Citation
“…), may feed on non‐vascular plants, i.e. algae and lichens, suggesting that the importance of non‐vascular plants as a basal resource of soil food webs has been underestimated (Schmidt et al ., ; Potapov et al ., ; Potapov et al ., ). Supporting the importance of non‐vascular plants in soil food webs, a recent DNA‐based study showed that algivory is widespread among soil protists (Seppey et al ., ).…”
Section: Reconstructing Trophic Linksmentioning
confidence: 98%
“…However, recent laboratory studies did not find Δ 15 N values to vary with food quality (Heethoff & Scheu, ). Another explanation might be the assimilation of resources depleted in 15 N. For instance, algae and lichens incorporate 15 N‐depleted atmospheric N deposits (Tozer et al ., ) and may channel this nitrogen to animal consumers in the soil (Schmidt, Dyckmans & Schrader, ; Potapov, Korotkevich & Tiunov, ).…”
Section: Trophic Enrichmentmentioning
confidence: 99%
“…Figure prepared using the R package bipartite feed on algae, with on average algal biomarker FAs comprising 6% of total NLFAs in Collembola and 4% in Oribatida. Photoautotrophic algae and bacteria may represent a considerable portion of the diet of Collembola in various habitats (Potapov, Korotkevich, & Tiunov, 2018;Schmidt, Dyckmans, & Schrader, 2016). A high palatability of algae for Collembola and Oribatida was demonstrated in laboratory experiments (Brückner, Schuster, Smit, & Heethof, 2018;Buse, Ruess, & Filser, 2013Scheu & Folger, 2004) and field stable isotope-based studies from temperate forest ecosystems suggested that algae serve as food resource for certain species of Collembola and Oribatida (Schneider et al, 2004;Maraun et al, 2011;Potapov, Semenina, Korotkevich, Kuznetsova, & Tiunov, 2016).…”
Section: Food Resources Of Different Groups Of Soil Faunamentioning
confidence: 99%
“…However, Ngosong, Raupp, Scheu, and Ruess (2009) F I G U R E 4 Channeling of energy from basal resources into consumers in rainforest, rubber and oil palm plantations as indicated by fatty acid analysis. Photoautotrophic algae and bacteria may represent a considerable portion of the diet of Collembola in various habitats (Potapov, Korotkevich, & Tiunov, 2018;Schmidt, Dyckmans, & Schrader, 2016). The width of boxes/pictures of basal resources reflects the relative importance of these resources across land-use systems; note that it ignores potential differences in production and assimilation rate of different NLFAs among producer and consumer groups.…”
Section: Food Resources Of Different Groups Of Soil Faunamentioning
confidence: 99%
“…The increased interest in the role of green algae in terrestrial ecology (Buse et al, 2013;Schmidt et al, 2016) and ecotoxicology has emphasized the need for simple and objective methods of measuring their growth. Counting algae cells is the most popular method to estimate algae growth (Nyholm, 1990;Nyholm and Damgaard, 1990;Grote et al, 2005;Matzke et al, 2008), using either a counting chamber under the microscope or an automatic cell counter.…”
Section: Introductionmentioning
confidence: 99%